Disability in Peru and accessibility adjustments of spaces and infrastructure of inclusive educational centers - Mendoza Carrasco, Mariella Victoria (2018)
In Peru, there is around 1.5 million people with disabilities. But, according to the information from the World Health Organization (WHO), they are about 4.5 million people. Most of them, unfortunately, face a series of barriers to participate in social life, both behavioral and physical environment, which makes this group one of the most discriminated and excluded in our country. Unfortunately, in the current situation of the country, children with disabilities can not fully access education, either due to there is not the necessary infrastructure in educational centers, or due to the methodology of the schools and/or universities does not respond to their particular needs.